TRANSFERRING CULTURAL KNOWLEDGE IN LOCAL NARRATIVE READING FOR EFL STUDENTS - Ferri Hidayad; Marleni Marleni (Esteem Journal of English Education Study Programme, 2021)
Indonesia  has  many  narrative  reading  and  different  culture  of  many  regions. Lacking of appreciation of own local culture  is  a  continuing  concern  for  many  countries, including Indonesia.  Through  its  constitution,  the  governement  of  Indonesia  recommends  that  the education sector take part actively  in  preserving  Indonesia  local  cultures.  EFL  teachers should use them in their teaching and learning process as one of the resources to apply to preserve culture for younger generations (EFL students).  This  research  used  local  narrative reading to able the EFL teachers to preserve Indonesia culture as well as to transfer culture knowledge which makes their students study English and its culture with ease.